Deserto na comunicação: as relações entre ciência e mídia na desertificação do semiárido brasileiro - Ferreira, Luana Carlos (2017)
Being a serious environmental issue, the addressing of desertification relies on scientific understanding of its complex ecological, social and climatic relations. Caatinga is a unique biome in the Semi-arid region of Brazil still uncharted by science and its soil fertility and biodiversity face serious threat as desertification advances and jeopardizes food and water resources for thousands of people, which leads to migration influx. Governmental response has not been able to yield substantial actions to tackle the issue and society unfortunately seems not to sense the urge of such matter. One way to promote social engagement about the subject has to do with propagating related information in spite of political and economical interests lurking the narrative of mass media in Brazil. The focus of this paper is to analyze the narrative of Brazilian press regarding desertification, also including a view on science press. A panorama of scientific production was made through scientometrical analysis of scientific papers published between 2005-2014 and content analyses of news and reports printed and published byFolha de São Paulo from 1994 through 2015. An increase of scientific production for disciplinary purposes was noticed, although discontinued eventually as access to most papers on major national and international databases remain unreachable. On printed newspaper, approach to the subject is rare and often happens in a decontextualized or catastrophic-toned manner, not allowing space for opposite views, hence offering little voice to scientists and almost none to society. Thus, it becomes necessary to invest in long term multidisciplinary, solution-oriented, researches that deepen comprehension of subject matter and enable society to take part in scientific discussion as well as formulating policies and managing strategies to tackle desertification with the aid of propagating continuous, critical and contextualized information.